A comparative study on the supply of applied human resources for regional labour market needs in China's private higher education. Issue 6 (December 2022) - Cao, Lei; Kusakabe, Tatsuya
The purpose of this study is to explore changing trends of the applied human resource (AHR) system in China's private higher education institutions (PHEIs) and to examine the supply of AHRs by considering the dimensions of regional labour demand. The study specifically assesses the AHR demand of regional employment enterprises and the human resource development goals and related curricula in the three branches of PHEIs. It also analyses the employment situation of PHEI graduates and whether they address the actual AHR supply needs of the regional labour market. Six PHEIs and nine enterprises as employers were investigated as the study population, combining qualitative and quantitative data. The findings indicate that China's PHEIs quickly identified and overcame the challenges in their previous student cultivation goals and relevant curricula by researching the regional situation and taking responsibility for meeting demand. As a result, the PHEIs worked on developing transformative human resource systems through various initiatives. Moreover, these transformations of educational content worked in conjunction with a process that matched the graduates with jobs at regional enterprises. The transformed PHEIs are beginning to provide a human resource supply system that successfully expands the AHR supply from the various categories of PHEIs in the region.